Sacral agenesis combined with spinopelvic dissociation: A case report and literature review - Zhang, Haiping (Medicine (Baltimore), 2018)
INTRODUCTION: Sacral agenesis is a rare congenital disease with radiologic manifestation of sacrum deformity. Its clinical manifestations include spinopelvic instability due to sacroiliac joint deformity, spinal rotation, scoliosis, difficulties in walking, and claudication. Surgical intervention aims to prevent further deformity progression and to improve the patients’ walking function. It is challenging to achieve solid arthrodesis for this congenital disease, and fusion failure could aggravate deformity. CASE PRESENTATION: We retrospectively studied one case of a 12-year-old girl with sacral agenesis combined with spinopelvic dissociation and spinal scoliosis. She was presented with intermittent lumbosacral pain and worsening walking instability. We reconstructed the posterior pelvic ring through 1 iliac screw implanted in the bilateral posterior superior iliac spine, and the preflexed connecting rod was tightly locked with bilateral screws through the opening at the right spinal process of S2. With this method, bilateral ilia and sacrum were integrated and hemipelvic floating could be corrected. Bone fusion was achieved between the bilateral ilia and the sacrum. CONCLUSION: Ilium-sacrum-ilium internal fixation and fusion for treating sacral agenesis combined with spinopelvic dissociation could achieve sacroiliac joint fusion. It is easy to perform and could cause little trauma while preserving the lumbar motion segment, which will provide new insight for treating sacral agenesis.